An impedance spectroscopy ASIC for low-frequency characterization of biological samples - Montero-Rodríguez, Juan J.; Salazar-Flórez, Edgar Eduardo; Vega-Castillo, Paola; Tomasik, Jakob M.; Galjan, Wjatscheslaw; Hafkemeyer, Kristian M.; Krautschneider, Wolfgang (Scopus, 2016)
This paper describes the design and testing of an ASIC for impedance spectroscopy of biological samples at frequencies up to 40 kHz. The circuit is designed in the 350 nm AMS H35B4 technology and enables the measurement of impedances in the range of 10 kW up to 28 MW. The design features a digital oscillator and a current-to-voltage converter. The ASIC is used to monitor the growth of yeast cell cultures and porcine chondrocytes, in real-time, using a standard 384-well plate and copper electrodes.
Artículo
Keywords: ASIC; Concentración; Levadura; espectroscopia; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics